America in Rome: Race, Stereotypes, and Cultural Identities in the Series Home Sweet Rome! - Minguzzi, Carolina Caterina (Italian Canadiana)

(untitled) (Iter Press, 2025)
“Home Sweet Rome!” (2023–to present), a Canadian–Italian co-production aimed at a young audience, provides an emblematic case for examining the circulation of cultural identities and racial representations in contemporary transnational media. The series follows Lucy, an American teenager who moves to Rome with her father and his new Italian wife. The series also introduces audiences to Charlotte, Lucy’s Franco-American and Afro-descendant classmate, who embodies a transatlantic identity that challenges traditional narratives of ethnicity and belonging and functions as a crucial counterpart to the protagonist. Drawing on cultural studies and Black diaspora studies, this article analyzes key sequences selected from several episodes, with a focus on framing, editing, music, and online audience reception. Positioned within the context of international co-productions and platform-based production models, Home Sweet Rome! emerges as a hybrid text mediating between local and global logics. The aim of the article is to show how the series, while following the conventions of preteen entertainment, challenges stereotypes and explores complex dynamics of cultural identity and social integration. In this sense, Home Sweet Rome! becomes a site of negotiation for transnational identities and new, albeit ambiguous, forms of inclusion within European media culture.